2009
DOI: 10.2298/gensr0902199p
|View full text |Cite
|
Sign up to set email alerts
|

Spike stability parameters in wheat grown on solonetz soil

Abstract: Phenotypic variability of the number and grain weight per spike, as well as the spike length of wheat varieties NSR-5, Evropa 90 and Pobeda creation of the Institute of Field and Vegetable Crops in Novi Sad was studied. The trial was conducted at the village Kumane locality in Banat on solonetz soil. Control and two levels of amelioration (25t/ha and 50t/ha of phosphor gypsum) in three vegetation periods were followed. The variety Evropa 90 exhibited maximal values of all examined spike traits in all years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…Grain weight per spike, together with numerous traits, contributes to the formation of total grain yield (KNEZEVIC et al, 2015). Therefore, this trait can be included in the indirect indicators of grain yield (PETROVIC et al, 2009). According to ROHANI and MARKER (2016b) correlation between yield and its components presents a confusing picture due to interrelationships between component characteristics by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Grain weight per spike, together with numerous traits, contributes to the formation of total grain yield (KNEZEVIC et al, 2015). Therefore, this trait can be included in the indirect indicators of grain yield (PETROVIC et al, 2009). According to ROHANI and MARKER (2016b) correlation between yield and its components presents a confusing picture due to interrelationships between component characteristics by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The AMMI model is utilized for three main purposes (Gauch, 1988;Crossa et al, 1990): (i) to suitable in the initial statistical analyses of yield experiments, (ii) to summarize the relationships between genotypes and environments (GE) and (iii) to applicable for understanding complex genotypes × environment interaction effects. AMMI analysis has been applied extensively with great success to interpret genotype × environment interaction in wheat (Petrovic et al, 2009;Petrovic et al, 2010;Mahmoodi et al, 2011;Oikeh et al, 2004;Mohammadi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Deitos et al (2006) indicate that G×E interaction is important in breeding process because it influences the genetic gain, as well as the recommendation and choosing the varieties with high adaptability. Petrović et al (2009) concluded that breeding for the targeted environment highly depends on the identification of the major sources of phenotypic variation in that region. In order to develop a variety or a hybrid which possess lower G×E interaction, for the dominant sources of variation, variety should have the balanced proportion between stabile and high yield (Boakyewaa, 2012).…”
Section: Academicpresmentioning
confidence: 99%